Two dimensional computational model coupling myoarchitecture-based lingual tissue mechanics with liquid bolus flow during oropharyngeal swallowing. (June 2022) - Leichter, Dana M.; Stark, Nicole E.; Leary, Owen P.; Brodsky, Martin B.; Gilbert, Richard J.; Nicosia, Mark A.
Abstract: Biomechanical relationships involving lingual myoanatomy, contractility, and bolus movement are fundamental properties of human swallowing. To portray the relationship between lingual deformation and bolus flow during swallowing, a weakly one-way solid-fluid finite element model (FEM) was derived employing an elemental mesh aligned to magnetic resonance diffusional tractography (Q-space MRI, QSI) of the human tongue, an arbitrary Lagrangian-Eulerian (ALE) formulation with remeshing to account for the effects of lingual surface (boundary) deformation, an implementation of patterned fiber shortening, and a computational visualization of liquid bolus flow. Representing lingual tissue deformation in terms of its 2D principal Lagrangian strain in the mid-sagittal plane, we demonstrated that the swallow sequence was characterized by initial superior-anterior expansion directed towards the hard palate, followed by sequential, radially directed, contractions of the genioglossus and verticalis to promote lingual rotation (lateral perspective) and propulsive displacement. We specifically assessed local bolus velocity as a function of viscosity (perfect slip conditions) and observed that a low viscosity bolus (5 cP) exhibited maximal displacement, surface spreading and local velocity compared to medium (110 cP, 300 cP) and high (525 cP) viscosity boluses. Analysis of local nodal velocity revealed that all bolus viscosities exhibited a bi-phasic progression, with the low viscosity bolus being the most heterogeneous and fragmented and the high viscosity bolus being the most homogenous and cohesive. Intraoral bolus cohesion was depicted in terms of the distributed velocity gradient, with higher gradients being associated with increased shear rate and bolus fragmentation. Lastly, we made a sensitivity analysis on tongue stiffness and contractility by varying the degree of extracellular matrix (ECM) stiffness through effects on the Mooney-Rivlin derived passive matrix and by varying maximum tetanized isometric stress, and observed that a graded increase of ECM stiffness was associated with reduced bolus spreading, posterior displacement, and surface velocity gradients, whereas a reduction of global contractility resulted in a graded reduction of obtainable accommodation volume, absent bolus spreading, and loss of posterior displacement. We portray a unidirectionally coupled solid-liquid FEM which associates myoarchitecture-based lingual deformation with intra-oral bolus flow, and deduce that local elevation of the velocity gradient correlates with bolus fragmentation, a precondition believed to be associated with aspiration vulnerability during oropharyngeal swallowing. Highlights: Two-dimensional coupled model fluid-structure model of bolus flow. Lingual motions based on model of muscle contractions utilizing muscular myoarchitecture. Model provides ability to study bolus flow outcomes for disordered swallowing.